2015 Symposium on VLSI Circuits (VLSI Circuits) 2015
DOI: 10.1109/vlsic.2015.7231381
|View full text |Cite
|
Sign up to set email alerts
|

Highly reliable TaO<inf>x</inf> ReRAM with centralized filament for 28-nm embedded application

Abstract: For 28-nm embedded application, we have proposed a TaO x -based ReRAM with precise filament positioning and high thermal stability. The cell was realized using several newly-developed process technologies and cell structures: low-damage etching, cell side oxidation and encapsulated cell structure. As a result, we succeeded for the first time in forming a filament at the cell center. In addition, we confirmed the feasibility of 20-nm cell size. Excellent reliability was achieved in 2-Mbit 40-nm ReRAM: 100k cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Among the various transition metal oxide materials, tantalum oxide and hafnium oxide are consistently and unanimously investigated as the most promising materials systems for emerging memory technology and are among the most mature resistive materials explored . Both HfO x /TaO x ‐based RRAM show excellent resistive behavior . Besides, they have the potential to form a multi‐bit memory cell .…”
Section: High‐speed and Scalable Rram Cells And Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various transition metal oxide materials, tantalum oxide and hafnium oxide are consistently and unanimously investigated as the most promising materials systems for emerging memory technology and are among the most mature resistive materials explored . Both HfO x /TaO x ‐based RRAM show excellent resistive behavior . Besides, they have the potential to form a multi‐bit memory cell .…”
Section: High‐speed and Scalable Rram Cells And Systemsmentioning
confidence: 99%
“…Park et al demonstrated a lightning rod effect in filamentary switching RRAM could confine the random formation of filaments, thus improving switching uniformity . Hayakawa et al demonstrated a TaO x RRAM with precise filament positioning by forming an encapsulated cell structure . Li et al reported a reduction of variation and forming/set voltage can be achieved through enhanced electrical field by a pyramid‐like electrode .…”
Section: High‐speed and Scalable Rram Cells And Systemsmentioning
confidence: 99%
“…RRAM devices are especially attractive due to their good compatibility with logic processes. For instance, an embedded RRAM solution has been introduced for a 28-nm technology node [64], [65]. Therefore, RRAM has great potential as MB-level embedded NVM for micro-controller applications.…”
Section: Niche Market Of Emerging Nvmsmentioning
confidence: 99%
“…Special care has to be taken in order to mitigate the possibility for the CF to be formed close to the edges of the device (where these damages are present). This approach has been recently proposed for the precise positioning of the CF in a 28-nm integrated TaO x -based device [78].…”
Section: Vcm Device Optimizationmentioning
confidence: 99%